Impact of Work-Life Balance Management on Expatriates’ Career - Osah, Dennis; Šarkiūnaitė, Ingrida (Vilnius University Open Series, 2022)
As organizations go global by trying to increase revenues or penetrate new markets for expansion, it becomes necessary to have employees who will work overseas. Working overseas as an expatriate requires a lot of effort both from the expatriate and the organization in order for the assignment to be successful. Work-life balance is vital in this regard. Employees will only succeed in the official assignment when their organizations prioritize their well-being, as this will greatly assist them in making sure they are effective and efficient in their work. The goal of this research was to see how work-life balance impacts expatriates’ careers and whether there are any relationships between work-life balance and expatriates’ careers. Results showed work-life balance has a significant positive effect on performance. This is to say that a healthy work-life balance will impact an expatriates’ career greatly, which will also benefit the organization.